1959
DOI: 10.1002/hlca.19590420408
|View full text |Cite
|
Sign up to set email alerts
|

Organische Derivate des Silikagels mit SiC‐Bindung II

Abstract: Organic derivatives of silica were prepared by treating silica with triphenyl‐ and trimethylchlorosilane or with hexamethyldisilazane. The trimethylsiloxy derivatives are extremely hydrophobic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1959
1959
1986
1986

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Trimethylsilyl groups can also be grafted to the silica surface by reaction with hexamethyldisilazane, Me 3 Si-NH-SiMe 3 [622,623]. The reaction has an even faster rate than that with trimethylchlorosilane [624].…”
Section: B) Surface Esters and Surface Amidesmentioning
confidence: 97%
“…Trimethylsilyl groups can also be grafted to the silica surface by reaction with hexamethyldisilazane, Me 3 Si-NH-SiMe 3 [622,623]. The reaction has an even faster rate than that with trimethylchlorosilane [624].…”
Section: B) Surface Esters and Surface Amidesmentioning
confidence: 97%
“…It is shown that crosslinking these systems results in an increase in thermal and chemical stability and prevents the polymer from excessive swelling [57,58,[83][84][85][86]. A PI membrane can be cross-linked by radical initiation, through thermal treatments, by UV irradiation [84,87] or by chemical crosslinking [57,58,[88][89][90][91]. For SRNF, radical initiation is not suitable, because crosslinking cannot be throughout the whole membrane.…”
Section: Polymeric Membranes As Snrfmentioning
confidence: 99%
“…Reaction with mono-, di-and trifunctional organosilanes are of particular interest. Apart from good thermal stability, such layers also resist in some extend to hydrolytic degradation, especially with increasing surface coverage [87]. Modification of a surface can be achieved either by: • • Exposing it directly to a silane vapor (vapor phase reaction).…”
Section: Silylation Reaction Mechanism and Influence Of The Reaction mentioning
confidence: 99%
“…If the primary organic layer attached to the silica (such as a Porasil) is itself reactive, such as an aromatic hydrocarbon, its reactivity can in principle be used to introduce further substitution of any desired functionality and/or chain length, and therefore a wide range of chromatographic selectivities. Grignard reactions with chlorosilanes have long been known (7), and a butyl derivative of silica gel has been prepared via such a reaction (8,9). To our knowledge, however, the present work is the first to apply the reaction to the preparation of substrates for chromatography.…”
mentioning
confidence: 94%